Iron times and golden ages: nostalgia and the Mid-Victorian historical novel - Cassidy, CM (2014)
This thesis examines nostalgia as a central literary trope of burgeoning modernisation in the mid-Victorian historical novel. Nostalgia began as a pathological form of homesickness and rapidly engaged with the perceived distancing from the past brought about by accelerated modernisation. This thesis suggests that literary representations of social, cultural and technological change echo nostalgic reactions of loss and longing. Charles Dickens, William Makepeace Thackeray, Elizabeth Gaskell and George Eliot are the primary focus of this study. Selected works by these authors are situated within the wider context of Victorian historical fiction which – following Walter Scott’s phenomenal success at the beginning of the century – became, as Franco Moretti put it, a ‘key genre’ in the Victorian era. Nostalgia’s first victims were soldiers and students displaced from home by new opportunities for mobility and new reasons to travel long distances and live away from home; it was a disease that responded to modernisation or, as Kevis Goodman has put it, ‘historical growing pains’. Nostalgia’s combination of historical and psychological dimensions, I argue, made it an aesthetic peculiarly suited to the historical novel. This thesis suggests that nostalgia was an important novelistic trope during the nineteenth century and argues that it quickly became enmeshed with the historical novel in a way that has seldom been acknowledged. Because of its medical origins, alongside its continued development as a poetic trope, nostalgia provided a language with which to intertwine emotional and psychological reactions to change with the fictional representation of real historical events. The thesis begins with a detailed account of nostalgia’s etymological history, scientific entanglements and early literary manifestations; the introduction establishes the theoretical and historical framework for the thematically organised chapters that follow. Chapter 1 explores the interlacing of personal and historical subject matter in Thackeray’s historical fiction. This chapter suggests that these interactions took place in Thackeray’s historical fiction through the mingling of nostalgic tropes in the person of his central protagonists. These figures frequently follow Scott’s Edward Waverley in being insipid spectator-participants who have been displaced from their homes and (directly or indirectly) mediate events from a perspective of nostalgic exile. Chapter 2 considers the transformation of landscape as a node of nostalgic representation. It explores the confusion of time and place in the original case studies collected by doctors studying nostalgia as a disease in relation to nineteenth-century representations of past landscapes. It suggests that part of the historicising potential of geographical places comes from this instinctive association of time with place. This overlap is exploited in the historical novel to represent changing times via changing places. Chapter 3 takes George Eliot’s Romola, frequently criticised both by contemporary commentators and subsequent critics for being too full of minutely researched objects, as a illustrative example of how things can become ‘memorative signs’ around which to build a narrative. This ‘clutter’ is reinterpreted as a system of souvenirs, artefacts and mementoes through which public history is reconstructed from excavated fragments of private life. Chapter 4 explores how mid-Victorian historical fiction tested the limits of its own nostalgic tropes. It uses Sylvia’s Lovers to probe the point at which forgetfulness overtakes the most carefully memorialised people and events. It discusses the ways in which these novels use nostalgia to represent a perilous closeness between memorialisation and erasure. It considers whether a trope premised on loss might require the threat of encroaching historical oblivion to complete its own metaphors. The thesis concludes with a coda looking forward to later nineteenth-century uses of nostalgia in historical fiction through a reading of Thomas Hardy’s The Trumpet Major (1880) and The Mayor of Casterbridge (1886).